Gas around galaxy haloes - II: hydrogen absorption signatures from the environments of galaxies at redshifts 2<z<3 - Meiksin, Avery; Bolton, James S.; Tittley, Eric (Oxford University Press, 2015)
We compare predictions of large-scale cosmological hydrodynamical simulations for neutral hydrogen absorption signatures in the vicinity of 1011–1012.5 M⊙ haloes with observational measurements. Two different hydrodynamical techniques and a variety of prescriptions for gas removal in high-density regions are examined. Star formation and wind feedback play only secondary roles in the H i absorption signatures outside the virial radius, but play important roles within. Accordingly, we identify three distinct gaseous regions around a halo: the virialized region, the mesogalactic medium outside the virial radius arising from the extended haloes of galaxies out to about two turnaround radii and the intergalactic medium beyond. Predictions for the amount of absorption from the mesogalactic and intergalactic media are robust across different methodologies, and the predictions agree with the amount of absorption observed around star-forming galaxies and quasi-stellar object host galaxies. Recovering the measured amount of absorption within the virialized region, however, requires either a higher dynamic range in the simulations, additional physics, or both.